Artificial Intelligence and Its Role in Sustainable Development (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has emerged as a transformative technology that offers immense potential to address global challenges, particularly in the context of sustainable development. By leveraging AI's capabilities in data processing, automation, and optimization, there is significant promise in achieving sustainability goals across various sectors, including healthcare, energy, agriculture, and climate change mitigation. This paper explores the relationship between AI and sustainable development, highlighting the potential applications of AI technologies to promote social, economic, and environmental sustainability. Through an examination of current AI applications, case studies, and future directions, this paper also explores the ethical implications of AI deployment in these critical areas. The study emphasizes the importance of responsible AI development and ethical guidelines to ensure that AI contributes to sustainable and equitable development outcomes. The findings underscore the need for policy frameworks that support AI-driven sustainability initiatives while addressing challenges related to bias, privacy, and environmental impacts.